Producció escrita i producció oral - Martí i Castell, Joan (Caplletra. Revista Internacional de Filologia, 2015)
The autor evaluates written documents and oral linguistic production in order to study the development of language and linguistic change, and regrets the fact that have little influence on historical linguistics.